2000
DOI: 10.1509/jmkg.64.1.67.17993
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Orientation and Firm Performance in an Artistic Environment

Abstract: Conventional marketing wisdom holds that a customer orientation provides a firm with a better understanding of its customers, which subsequently leads to enhanced customer satisfaction and firm performance. However, there are cautions that being too customer focused can lead to inertia, and anecdotal evidence suggests that it may be better to "ignore your customer" when developing new products. Building on the market orientation research stream, the authors examine the impact of three alternative strategic ori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
440
4
36

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 542 publications
(517 citation statements)
references
References 57 publications
(129 reference statements)
20
440
4
36
Order By: Relevance
“…Some creative industries may have international audiences, but the survival and development of their constitutive professional organizations -e.g. museums (Alexander, 1996), theaters (Voss & Voss, 2000), and philharmonic orchestras (Durand & Kremp, 2015) -remain highly dependent on and constrained by national socio-political and economic arrangements. To conduct our research, we needed a creative industry with many comparable actors, with well-established, salient and sedimentary professional norms and with a high degree of exposure to a national cultural policy.…”
Section: The Theater Industry In Russia As a Setting To Understand Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Some creative industries may have international audiences, but the survival and development of their constitutive professional organizations -e.g. museums (Alexander, 1996), theaters (Voss & Voss, 2000), and philharmonic orchestras (Durand & Kremp, 2015) -remain highly dependent on and constrained by national socio-political and economic arrangements. To conduct our research, we needed a creative industry with many comparable actors, with well-established, salient and sedimentary professional norms and with a high degree of exposure to a national cultural policy.…”
Section: The Theater Industry In Russia As a Setting To Understand Thmentioning
confidence: 99%
“…This friction is fueled by the fact corporate interests are traditionally despised by the intellectual and cultural elite of Russia. Only a limited amount of management research has looked at the theater industry outside the empirical work by Glenn and Zannie Voss (among which Voss & Voss, 2000or Voss et al, 2008 our study however takes a more macro approach to this field, which makes our peculiar national context an asset.…”
Section: Generalizability Limitations and Future Researchmentioning
confidence: 99%
“…For example, over the previous 17 years, various researchers (Appiah-Adu, 1997) have examined the effects of MO on firm performance, advocating positive (Kumar, Subramanian, & Yauger, 1998), negative (Voss & Voss, 2000), and nonsignificant findings (Greenley, 1995). Even though Rodriguez-Cano, Carrillat and Jaramillo (2004) supported a positive relationship between MO and enterprise performance in their meta-analysis, other reviews (e.g., Langerak, 2003) have culminated in inconclusive results, suggesting that the relationships are not so straight forward (Olavarrieta & Friedmann, 2008).…”
Section: Market Orientation and Firm Performancementioning
confidence: 99%
“…The study conducted by Voss and Voss (2000) revealed that there is correlation between subjective and objective performance measurement. It means that the company performance can be measured by using a subjective measurement.…”
Section: Company Performancementioning
confidence: 99%